DINAMISASI HUKUM ISLAM: SUATU PENDEKATAN DALAM KERANGKA METODOLOGI USHUL FIQH - Winarno, Winarno (Nurani, 2016)
Islamic law broadly recognizes two kinds of sources oflaw, namely the source of law which is "naqli" and a source oflaw is the "aqli". Sources of law based on the proposition is theQur'an and al-Sunnah, while the source of the laws of logic isthe result of the effort to find the law by emphasizing theprocess to think with a variety of methods. Figures or imamsschools in exploring of legal values that not explicitly specifiesin detail and firm in the Qur'an and Sunnah, each of themoffers the methodological framework, the theory and principlesof ijtihad which became a reference in setting their law.Methodological framework in question is a methodologicalframework Usul Fiqh. Enterprises using ijtihad in issuing legalframework Usul Fiqh methodology is expected to produce legalproducts that are felt dynamic. This article will explore thedynamics of Islamic law with the rules of fiqh methodologyapproach.ملخص: یعترف القانون الإسلامي على نطاق واسع نوعین من مصادر القانون، التيھي مصدر القانون وھو" حجة الدین "ومصدر القانون ھو" المنطق ."مصادرالقانون بناء على اقتراح ھو القرآن و آل السنة، فیما أكد مصدر من قوانین المنطقھي نتیجة جھد للعثور على القانون مع التركیز على عملیة التفكیر مع مجموعةمتنوعة من الطرق .قادة أو الكھنة المدارس في استكشاف القیم القانونیة التي لم یتمتنظیمھا بشكل واضح في التفاصیل وشركة في القرآن والسنة، كل واحد منھم یقدمالإطار المنھجي والنظري ومبادئ الاجتھاد الذي أصبح مرجعا في محیطھم القانون .الإطار المنھجي في السؤال ھو إطار منھجي أصول الفقھ .ومن المتوقع أن تنتجمنتجات القانونیة التي شعرت دینامیكیة الشركات باستخدام الاجتھاد في إصدار الإطارالقانوني منھجیة أصول الفقھ .ھذه المادة سوف تستكشف دینامیات الشریعة الإسلامیةمع قواعد النھج منھجیة الفقھ.